Sustainability analysis of zero energy consumption data centers with free cooling, waste heat reuse and renewable energy systems: A feasibility study - Güğül, Gül Nihal; Gökçül, Furkan; Eicker, Ursula (Energy (Oxford), 2023)
The energy consumption of data centers (DC) has increased rapidly over the past years. Regional studies are an effective way to find the optimal integration of renewable energy, free cooling and waste heat recovery technologies to improve the energy efficiency of DCs. In this study, the feasibility of a net zero energy DC was evaluated. As a case study a bank DC in Kocaeli, Turkey was monitored hourly for 10 months and monthly for 12 months during 2020. The most feasible way to reach zero energy was found to be a free cooling system combined with a PV generator, which has the lowest payback period (PBP) of 6 years at minimum initial retrofit cost. The free cooling system resulted in 83% reduction in cooling demand and an improvement in power usage effectiveness from 1.8 to 1.1. The PBP was also 6 years for a waste heat reuse system and for an outdoor location of the same DC, but with a higher initial cost than free cooling system. While increasing the U-value from 0.1 to 3 W/m2K caused to an increase in cooling demand by 11% for the Kocaeli weather conditions, a decrease in cooling demand would occur in colder climates. •One year of monitored electricity consumption data of a bank data center is used.•Feasibility of reaching net zero energy consumption data center has been evaluated.•Free cooling, waste heat reuse, building and PV scenarios are applied.•Net zero energy goal is achieved with 6 years of PBP.